Discipleship, suffering and racial justice : mission in a pandemic world - Olofinjana, Israel (Regnum Books International, 2022)
"This book explores the subject of discipleship, suffering and racial justice and what the UK church can learn about these themes from the experiences and theologies of Majority World contexts. It argues powerfully that suffering is relative (relativity of suffering) and develops this as a discipleship theory needed during the pandemic and post-pandemic context. The book therefore examines post-colonial contextual theologies rooted in pain and how they can serve the Church during and post pandemic."--Publisher.